A porcine model of Fanconi anemia - Brandon Hergert; Kristin M. Whitworth; Devorah C. Goldman; Lisa Moreau; Kelsey McQueen; Kalindi Parmar; Alan D’Andrea; Melissa S. Samuel; Kevin D. Wells; Randall S. Prather; Craig Dorell; Markus Grompe; et al. (PLoS ONE, 2025)
Although small animal models of Fanconi anemia (FA) are useful, they do not faithfully replicate many of the clinical features seen in FA patients. We reasoned that a porcine model of FA with its similar physiology and a relatively long lifespan would produce a phenotype more similar to human FA. Targeting FANCA in domestic swine resulted in skeletal abnormalities and extreme sensitivity to interstrand DNA cross-linking agents. In addition, FANCA disruption followed by mitomycin C treatment resulted in a > 10-fold increase in chromosomal radials, a finding that is considered diagnostic for human FA. Bone marrow derived, hematopoietic progenitor cells from a FANCA null pig showed a 75% reduction in colony forming activity compared to wild type. Evaluation of steady state hematopoiesis in the peripheral blood revealed the gradual development of red cell macrocytosis and a reduction in circulating neutrophils. Targeting of FANCD2 failed to produce any biallelic animals demonstrating the loss of FANCD2 function is embryonic lethal in pigs. These results indicate that a porcine model of FANCA holds promise for the development of strategies to prevent the development of bone marrow failure and malignancies in patients with FA.